WATER QUALITY ANALYSIS AND POLLUTION LOAD CAPACITY OF RIVER KAPUAS IN MUKOK DISTRICT, SANGGAU REGENCY - Katarina Dwi Yanti (Universitas Tanjungpura, 2021)
The Kapuas River in Mukok District is a 22-kilometer-long branch of the Kapuas River in West Kalimantan Province. Various activities in Mukok District, Sanggau Regency, contribute to a decrease in the water quality of the Kapuas River. The purpose of this study is to inventory and identify pollution sources, calculate the Pollution Index, determine the potential pollutant load, and calculate the pollutant load capacity. The water quality standard used is class II, as defined by Government Regulation (PP) No. 28 of 2001. According to the findings of the identification and inventory, the sources of pollution on the banks of the Kapuas River in Mukok District, Sanggau Regency, are settlements, livestock, industry, rice fields, and oil palm plantations. The water quality standard of the Kapuas river in Mukok District, Sanggau Regency, based on the class II water quality standard, has exceeded the class II quality standard limit for parameters BOD, COD, DO, and Nitrate. The pollutant originating from oil palm plantations is the source of the potential pollutant load that enters the Kapuas river, Mukok District, Sanggau Regency. Overall, the Kapuas River in Mukok District, District is classified as lightly polluted, with pollution index values ranging from 2,082 to 3,231. The capacity of the pollutant load of the BOD and COD parameters exceeds the capacity, so it can no longer accommodate the load polluter. Meanwhile, the Kapuas River TSS parameter in Mukok District, Sanggau Regency can still handle a pollution load of 6.733.352,358 kg/day.